PENGARUH KUALITAS PRODUK DAN CITRA MEREK TERHADAP KEPUASAN KONSUMEN (Studi pada Toko Sepatu Bata MTC Giant Panam) - Wandry Simarmata; Meyzi Heriyanto (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study aimed to determain the effect of Product Quality and Brand Image on customer satisfaction (Study at MTC Giant Panam Bata Shoe Store). Product Quality and Brand Image as the independent variable (X1X2) while the costumer satisfaction as the dependent variable (Y). The problem in this research is the sales targets that did not reach the target in the past 5 years. Seen from the presentation realization shoe sales in the last 5 years. The research sample was taken of 100 respondents of the population was calculated using the Slovin formula. The data was getting from the questionnaire and subsequently processed to then be tested with statistics through SPSS. From the result which shows that quality product and brand image have a positive and significant impact on customer satisfaction (study at MTC Giant Panam Bata Shoe Store).   Keywords : quality product, brand image and customer satisfaction